(3JMUjd ZQV GdbGUO aj JaUjd GdeQV GdhGaOs - (3CMeO Hf Ydj Hf eMeO Hf NGJeI GdCfUGQj, CHhLYaQs
(3ChdgG (B:s
(3hHYO (B: (3aEf HYV CUObGFi ef jJYjf Ydi ESYGage hdG jSYfi NdGage, SGdhfi s
(3BNQgG (B:s
(3aQL Gddg Yf GdeSdejf eGge ajg ef Cdje GdcQHI hYXje NWHI HLGg GdYXje GdLGg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B19s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdChd (B- (3U (B39 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdYehejI (B(4085) s
(3JHUQI GdJQGLe(Bs
Keywords: (3GdWHs